Modern Concepts About Recurrent Bronchitis in Children (Literature Review) (Eurasian Research Bulletin, 2022)
In recent years, there has been an increase in the incidence of respiratory pathology, including recurrent and chronic respiratory diseases [2,5,11,14]. Thus, according to the scientists of Uzbekistan and world statistics, acute bronchopulmonary diseases account for 36% in the structure of general morbidity in children and 51% in the cause of infant mortality [11,17].